CO2 Mobility and CO2/Brine Interfacial Tension Reduction by Using a New Surfactant for EOR Applications - Sagir, M. (Taylor and Francis Inc., 2014)
The synthesis and use in enhanced oil recovery applications of a novel CO2-philic surfactant derived from maleic anhydride and 2-butyl-1-octanol is reported. The synthesis involved the esterification of maleic anhydride to produce diester followed by sulfonation of the esterified product. The esterification reaction parameters were optimized for the maximum yield of 98.4. By employing a silica sulfuric acid catalyst, the reaction kinetics of esterification were also investigated. The activation energy was found to be 45.58 kJ/mol. The sulfonation reaction of the esterified product was performed by using sodium bisulfite, and a yield of 82 of surfactant was achieved. The synthesized surfactant lowered the interfacial tension between CO2/brine to 3.1 mN/m and effectively reduced the CO2 mobility. This surfactant has a great potential to be used for CO2 mobility control for CO2-EOR applications. Â© 2014 Copyright Taylor & Francis Group, LLC.